Photoemission electron microscopy of electron donor and aceptor molecules for organic photovoltaics - Kose, Sinan (2017)
A series of samples based on acceptor and donor molecules used in organic photovoltaics were examined using photoemission electron microscopy (PEEM) in order to examine changes of morphology and to determine if PEEM spectroscopy can be used to determine the difference between acceptor and donor domains in the context of organic photovoltaics (OPVs). Cleaned Indium Tin Oxide (ITO) was examined using PEEM spectroscopy in order to obtain a cutoff value, the cutoff is related to the work function as it indicates the sample bias at which images begin to become detectable in the PEEM meaning electrons have been emitted from the surface. Samples with the acceptor and donor molecules in this case Poly(3-hexylthiophene-2,5-diyl) (P3HT) and Phenyl-C61-butyric acid methyl ester (PCBM) respectively were examined using PEEM spectroscopy with samples deposited using spin coating. Blends of the acceptor and donor were made by mixing appropriate proportions of the individual solutions of the acceptor and donor together. These mixtures were then spin coated onto a cleaned ITO substrate in order to examine the morphology as well as the cutoff values. The mixtures used were in the ratios: 1:1, 2:1, 1:0.8 P3HT:PCBM. In an effort towards more accurate model OPVs a sample of PDOT:PSS was examined using PEEM spectroscopy. The PEEM was determined to be able to distinguish between different materials on samples where appropriate, however the absolute values of work functions were not the expected values.